Metaverse and cultural preservation: an alternative through NFTs of social sustainability in Brazil - Silva, Manuella; Neto, Adolfo; Cabada, Carlos; Bland, Karina; Davanço, Jonas; Teixeira, João M. (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2023)
Exploring the potential of NFTs and metaverses can make them tools for cultural preservation and social sustainability in Brazil. This article provides an overview of the recent evolution of the metaverse and the adoption of these technologies by Brazilian communities. The main focus of this study is on the involvement and inclusion of Indigenous peoples in this technological sphere, emphasizing the importance of ensuring respect and preservation of forest peoples when including them in NFT projects. Several existing solutions that can facilitate social initiatives are exemplified, and one such solution is the 3.land marketplace/metaverse, which holds great potential for social actions due to its community-driven dynamics and 3D education promotion. The article concludes by suggesting possible directions to enhance technological development for Brazil’s Indigenous communities, promoting the appreciation and protection of cultural expressions from the forests through blockchain and cryptocurrency technologies.